Small signal stability enhancement of WSCC system using PSO based PSS - R. Ramya; K. Selvi; M.V. Suganyadevi; S. Usha (Franklin Open)
A number of synchronous generators are used in parallel in contemporary power systems. Studies are regularly carried out to make sure that the generators will work as intended in the case of any malfunctions or modifications to the system conditions. The tuning of the PSS parameters is one of the main challenges in the PSS use in the multi-machine power system for the improvement of tiny signal stability. The best tuning of power system stabilisers in multi-machine power systems has been extensively studied during the past 20 years. Multiple stabilisers must be utilised in multi-machine systems with poorly damped oscillation modes, and the challenge of setting the PSS parameters becomes comparatively challenging. This paper addresses the optimal tuning of the PSS parameters in the multi-machine power system by applying six different Particle Swarm Optimization methods such as AGPSO1, AGPSO2, AGPSO3, IPSO, MPSO and TACPSO. In the proposed work, Western System Coordinating Council (WSCC) system is considered. Three generator buses and six load buses make up the WSCC System. The remaining generators are considered to be connected in an infinite bus topology, and the synchronous generators used for the study are represented using a conventional IEEE Type 1 excitation system. The machine performance such as Terminal Voltage, Terminal Current, Real Power, Reactive Power, Rotor angle and Rotor speed are investigated with the PSO tuned PSS. The developed PSS is also tested for dynamic analysis with the variation in mechanical torque and reference voltage in real time simulation platform using dSPACE simulator.